Original paperHigh-dose-rate vaginal brachytherapy with chemotherapy for surgically staged localized uterine serous carcinoma - Damast, Shari; Higgins, Susan A.; Ratner, Elena; Leon, Maria C. De; Mani, Sheida; Silasi, Dan-Arin; Azodi, Masoud; Santin, Alessandro; Rutherford, Thomas; Schwartz, Peter E. (Journal of Contemporary Brachytherapy, 2015)
Purpose : To evaluate our institutional experience combining carboplatin-paclitaxel (C/T) chemotherapy with high-dose-rate (HDR) intra-vaginal brachytherapy (IVB) following comprehensive surgical staging in localized uterine serous carcinoma (USC). Material and methods : Institutional chart review identified 56 patients with FIGO 2009 stage I-II USC treated between 2000-2010. Patients underwent total hysterectomy, bilateral salpingo-oopherectomy, and comprehensive surgical staging including pelvic and para-aortic lymph node dissection, omentectomy, and peritoneal cytology. Chemotherapy was 6 cycles of C/T, and the IVB dose was 14 Gy in 2 fractions, prescribed to 0.5 cm from the cylinder surface. Kaplan-Meier methods were used to estimate recurrence-free survival (RFS) and overall survival (OS). Results : The median follow-up time was 49 months (range: 9-145). The 5-yr RFS and OS were 85% and 93%, respectively. In all cases of recurrence (n = 8), the first site of failure was extra-pelvic. There were no isolated vaginal recurrences, however, there was one vaginal apex recurrence recorded at 19 months in a patient with simultaneous lung metastases. Thus, the 2-year vaginal RFS was 98%. Conclusions : Excellent vaginal/pelvic control rates were observed. Further study of HDR brachytherapy dose and fractionation in combination with chemotherapy is worthwhile.